Plumbing 201 : PHCC educational Foundation plumbing apprentice & journeyman training committee / Plumbing-Heating-Cooling Contractors--National Association (U.S.). Educational Foundation - Plumbing-Heating-Cooling Contractors--National Association (U.S.). Educational Foundation
Offers practical knowledge and skills grounded in the real-world issues that face plumbing professionals. This volume provides information on piping materials, sources, and distribution for potable water; water pipe sizing; cross-connection protection; water heaters; sewage disposal; drainage fixture units; building drains; stacks; and more.